2020
DOI: 10.7717/peerj-cs.295
|View full text |Cite
|
Sign up to set email alerts
|

Text-mining forma mentis networks reconstruct public perception of the STEM gender gap in social media

Abstract: Mindset reconstruction maps how individuals structure and perceive knowledge, a map unfolded here by investigating language and its cognitive reflection in the human mind, i.e., the mental lexicon. Textual forma mentis networks (TFMN) are glass boxes introduced for extracting and understanding mindsets’ structure (in Latin forma mentis) from textual data. Combining network science, psycholinguistics and Big Data, TFMNs successfully identified relevant concepts in benchmark texts, without supervision. Once vali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
145
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(148 citation statements)
references
References 59 publications
(227 reference statements)
0
145
0
3
Order By: Relevance
“…This manuscript adopted the recent framework of forma mentis networks-as already introduced in previous studies-that used automatic text processing for reconstructing how social media discussed the gender gap in science [5] and for exploring online perceptions and emotions in Italy after the release of national lockdown [13]. On the one hand, [5] also showed that textual forma mentis networks in annotated texts are successful in determining the topic of a text. On the other hand, [13] showed that textual forma mentis networks are sensitive enough to highlight flickering emotions over time in the social discourse around specific topics and hashtags.…”
Section: Forma Mentis Network As Knowledge Graphs Extracted From Textmentioning
confidence: 99%
See 4 more Smart Citations
“…This manuscript adopted the recent framework of forma mentis networks-as already introduced in previous studies-that used automatic text processing for reconstructing how social media discussed the gender gap in science [5] and for exploring online perceptions and emotions in Italy after the release of national lockdown [13]. On the one hand, [5] also showed that textual forma mentis networks in annotated texts are successful in determining the topic of a text. On the other hand, [13] showed that textual forma mentis networks are sensitive enough to highlight flickering emotions over time in the social discourse around specific topics and hashtags.…”
Section: Forma Mentis Network As Knowledge Graphs Extracted From Textmentioning
confidence: 99%
“…Here, the methodology of textual forma mentis networks is reported in a concise yet self-contained manner. Based on cognitive data and text processing, forma mentis networks are knowledge graphs [5] representing the mental lexicon, a cognitive system storing linguistic information and driving word acquisition and use [6,9]. Representing conceptual associations between words as a network of nodes (words) and links (syntactic/semantic associations), textual forma mentis networks (TFMNs) extract both knowledge and affective patterns, as embedded in the text and are representative of a given author's mindset.…”
Section: Forma Mentis Network As Knowledge Graphs Extracted From Textmentioning
confidence: 99%
See 3 more Smart Citations